Chronosequence in Almar River fluvial-terrace soil - Dorronsoro, C; Alonso, P (Soil Science Society of America journal, 1994)
The aim of this work was to analyze how soils formed fundamentally from the erosion of granites evolve under a subhumid Mediterranean climate as a function of age. Their evolution was evaluated by means of the changes in components and properties, as well as the use of developmental indices. The sods are Xerorthents (Holocene), Haploxeralfs (Upper Pleistocene), and Palexeralfs (Middle Pleistocene). The properties have been subject to several trends: (i) some properties increase with regularity throughout the chronosequence (available water and coefficient of linear extensibility [COLE] of the Bt horizons) (ii) other properties increase strongly only during the first phases, while some continue to increase with age but only moderately (Ap horizon water retention and cation-exchange capacity, Bt horizon dithionite-citrate-extractable Fe, solum thickness, clay accumulation, quartz content, and quartz/feldspar ratio), whereas other Middle Pleistocene age soil properties cease to increase (the Ap horizon silt and available water, and Bt horizon water retention and cation-exchange capacity; (iii) others decrease with age, with pronounced decreases during the first phases (Ap and Bt horizon feldspar content and sand content and Bt horizon bulk density); and (iv) some properties are not age related (the Ap horizon base saturation and N content and the Bt horizon silt content). The horizon development indices and the soil development indices indicate good relationships with age. In most cases the rate of increase declines strongly for the oldest soils. In the great majority of cases, the properties and development indices continue to evolve through the chronosequence without reaching a steady state